Spaces for participation and exercise of citizenship, in the voice of associative leaders in the province of Cabo Delgado - Feijó, João (Observador Rural, 2023)
The text describes the historical obstacles to the development of civil society organizations (CSOs) in Mozambique, which experienced a more welcoming scenario in the 1990 Constitution. Mechanisms to support civil society empowered local leaders, making them better knowledgeable of legal provisions, capable of gathering evidence and making an impact on the population. However, the organizations faced internal problems, related to the lack of financial resources, the training of their members and problems of transparency and turnover. The education system develops few competencies of active citizenship, and the State is distrustful of initiatives to raise the awareness of the populations on fundamental rights or on mechanisms of civic participation. The maintenance of a political culture of subject has been functional to the penetration of big capital in the exploitation of natural resources. CSOs face obstacles to participation, related to the strong politicization of society, government distrust of public scrutiny, prohibition of public demonstrations and fear of their leadership, particularly after the beginning of the armed conflict. The spread of conflicts in extractive industry areas and the absence of formal channels for participation and access to justice intensified tensions, which were skilfully capitalized on by violent groups. The war dispersed the members of CSOs that were timidly flourishing in the various districts, taking away their organizational, advocacy and social pressure capacity. The arrival of international humanitarian organisations in response to the emergency included local associations, reproducing relations of assistance and dependency. The text demonstrates the urgency of identifying local leaders, (re)empowering CSOs and creating forums for social participation, reversing the belief that violence constitutes the possible and legitimate form of participation.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; security / segurança

Against the Odds: Action for Empowerment and Accountability in Challenging Contexts - Anderson, Colin; Gaventa, John; Edwards, Jenny; Joshi, Anuradha; Nampoothiri, Niranjan; Wilson, Emilie (Institute of Development Studies, 2022)
How and under what conditions does citizen-led social and political action contribute to empowerment and accountability? What are the strategies used, and with what outcomes, especially in settings which are democratically weak, politically fragile and affected by legacies of violence and conflict? The A4EA programme has explored these questions in Mozambique, Myanmar, Nigeria and Pakistan over five years between 2016-2021. This paper presents the key findings and policy and practice implications from this research across the themes of space for citizen action; citizen-governance relations; women’s political participation and collective action; citizen-led strategies for empowerment and accountability; and enabling citizen action. It also shares important lessons drawn from A4EA experience on conducting and communicating research in complex political contexts like these, and for research consortia. Whilst the research conclusions are drawn from A4EA’s four focus countries, in an increasingly fragile and authoritarian world, the findings are becoming pertinent for more and more contexts across the globe.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; L - english / inglês; citizenship & participation / cidadania e participação; civic space / espaço cívico; civil society / sociedade civil; conflict / conflito; governance / governação; mobilization / mobilização

Narrativas Desqualificadoras à Sociedade Civil em Moçambique e Sua Contribuição Para o Fechamento Do Espaço Cívico - Salimo, Padil; Monjane, Celso (2021)
O presente estudo visa identificar e analisar as narrativas dominantes de deslegitimação do papel da sociedade civil e sua contribuição para a obstrução do espaço cívico em Moçambique. O estudo também analisa como essas narrativas são disseminadas e as dinâmicas de poder que as sustentam. O estudo pretende providenciar estratégias que se contrapõem às narrativas desqualificadoras, e na construção de novas narrativas. Para o efeito, foram analisadas peças informativas ou opinativas nas redes sociais e media convencionais que evidenciam práticas manifestas de desqualificação da sociedade civil e com potenciais efeitos na obstrução e/ou no fechamento do espaço cívico. Associado a isso, faz-se o mapeamento dos propulsores dessas narrativas, os grupos a que pertencem e as suas motivações.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civic space / espaço cívico; civil society / sociedade civil

Navigating Civic Space in a Time of COVID-19: The Case of Mozambique - Pereira, Crescêncio; Forquilha, Salvador; Shankland, Alex (Institute for Social and Economic Studies, 2021)
This report builds on the Action for Empowerment and Accountability (A4EA) research project Navigating Civic Space, which seeks to analyze the extent to which COVID-19 is contributing to the opening or closing of space for civic action in three countries, namely Mozambique, Nigeria and Pakistan. Focusing on Mozambique, the report uses theoretical and methodological tools produced by the work stream and is essentially structured around the three main research questions: What is known about the civic space trend in Mozambique before the arrival of the COVID-19 pandemic?; How are different actors responding to the COVID-19 pandemic affecting the civic space in Mozambique?; What are the medium and long term implications for governance in Mozambique?
Keywords: G - Mozambique / Moçambique; L - english / inglês; civic space / espaço cívico; health - COVID-19 / saúde – COVID-19